SU(4) flavor symmetry breaking in D-meson couplings to light hadrons - Fontoura, C. E. [UNESP]; Haidenbauer, J.; Krein, G. [UNESP] (Springer, 2017)
The validity of SU(4)-flavor symmetry relations of couplings of charmed D-mesons to light mesons and baryons is examined with the use of P-3(0) quark-pair creation model and nonrelativistic quark-model wave functions. We focus on the three-meson couplings pi pi rho, KK rho and DD rho and baryon-baryon-meson couplings NN pi N Lambda K and N Lambda D-c. It is found that SU(4)-flavor symmetry is broken at the level of 30% in the DD rho tree-meson couplings and 20% in the baryon-baryon-meson couplings. Consequences of these findings for DN cross sections and existence of bound states D-mesons in nuclei are discussed.